2021
DOI: 10.3390/ijms22168631
|View full text |Cite
|
Sign up to set email alerts
|

The Oxoglutarate Binding Site and Regulatory Mechanism Are Conserved in Ammonium Transporter Inhibitors GlnKs from Methanococcales

Abstract: Protein inhibition is a natural regulatory process to control cellular metabolic fluxes. PII-family signal-transducing effectors are in this matter key regulators of the nitrogen metabolism. Their interaction with their various targets is governed by the cellular nitrogen level and the energy charge. Structural studies on GlnK, a PII-family inhibitor of the ammonium transporters (Amt), showed that the T-loops responsible for channel obstruction are displaced upon the binding of 2-oxoglutarate, magnesium and AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The genome of M. thermolithotrophicus harbors two different amtB genes with their associated glnK regulators (40). Interestingly, amtB1 and glnK1 were not differentially expressed (Supplementary Table 2, Figure 4A-B), which might point to the existence of an internal regulator or an additional promotor.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The genome of M. thermolithotrophicus harbors two different amtB genes with their associated glnK regulators (40). Interestingly, amtB1 and glnK1 were not differentially expressed (Supplementary Table 2, Figure 4A-B), which might point to the existence of an internal regulator or an additional promotor.…”
Section: Resultsmentioning
confidence: 96%
“…Series of incubations with different NH4Cl concentrations, ranging from 0.1 to 16.8 mM, showed that M. thermolithotrophicus required a minimum of 10 mM NH4Cl for best growth (Fig. 1A) in our optimized medium (see Materials and Methods for composition) (39,40).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations